Sebuah Tren Penelitian Laboratorium Virtual Berbasis STEM dalam Pembelajaran Sains dan Dampaknya terhadap Keterampilan Proses Sains melalui Analisis Bibliometrik (2020-2024) dan Kontribusi Indonesia - Bunaya Hanif Wintribrata; Dyah Rini Indriyanti; Fianti Fianti (Postgraduate, University of Mataram, 2025)
This paper aims to analyze the scientific trend of research on the impact of virtual laboratories on STEM-based science learning and their influence on students' science process skills through bibliometric study and to explore how the contribution of Indonesian researchers in the Scopus database from 2020 to 2024. The sample was composed of 7 documents in total. The results revealed that scientific publication on the impact of virtual laboratories on STEM-based science learning and their influence on students' science process skills has been increasing. In the last five years, seven countries have contributed to writing journal articles related to on the impact of virtual laboratories on STEM-based science learning and their influence on students' science process skills. The seven countries are Indonesia, Brazil, Rwanda, Zimbabwe, the United States, Spain, and Mexico. There is one journal from Indonesia that discusses on the impact of virtual laboratories on STEM-based science learning and their influence on students' science process skills in the last five years, namely a journal written by Usman et al. (2021) and published in the Journal of Physics: Conference Series, Yogyakarta State University, Indonesia. The research findings could aid related researchers to recognize the trend of impact of virtual laboratories on STEM-based science learning and their influence on students' science process skills research globally and recommend directions for further research.